Component analysis of nucleolar protein compartments using Xenopus laevis oocytes. (12th June 2022) - Lavering, Emily D.; Petros, Irini N.; Weeks, Daniel L.
Abstract: The nucleolus is a multi‐compartment, non‐membrane‐bound organelle within the nucleus. Nucleolar assembly is influenced by proteins capable of phase separation. Xenopus laevis oocytes contain hundreds of large nucleoli that provide experimental access for nucleoli that is unavailable in other systems. Here we detail methods to streamline the in vivo analysis of the compartmentalization of nucleolar proteins that are suspected of phase separation. The nucleolus is the main hub of ribosome biogenesis and here we present data supporting the division of proteins into nucleolar domains based on their function in ribosome biogenesis. We also describe the use of vital dyes such as Hoechst 33342 and Thioflavin T in nucleolar staining. Additionally, we quantify nucleolar morphology changes induced by heat shock and actinomycin D treatments. We suggest these approaches will be valuable in a variety of studies that seek to better understand the nucleolus, particularly those regarding phase separation. These approaches may also be instructive for other studies on phase separation, especially in the nucleus.